2023
DOI: 10.1038/s41598-023-35440-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between changes in echocardiography and risk of heart failure hospitalizations and death in adults with chronic kidney disease

Abstract: Adults with chronic kidney disease (CKD) are at increased risk for developing heart failure (HF). However, longitudinal cardiac remodeling in CKD has not been well-characterized and its association with HF outcomes remains unknown. We evaluated the association between change in echocardiographic parameters between baseline and year 4 with the subsequent risk of HF hospitalization and death using Cox proportional hazard models in a landmark analysis of a prospective multicenter CKD cohort. Among 2673 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Data from the Chronic Renal Insufficiency Cohort (CRIC) Study revealed a close interaction between cardiac structure and the risk of renal failure in a population with CKD, hypothesizing that cardiac abnormalities and renal damage are based on the same causal pathways, related to the interaction between hypertension, heart failure, and coronary artery diseases [5]. Furthermore, other prognostic evidence has been assessed among adults with CKD, revealing a causal link between adverse cardiac remodeling and increased risk of heart failure-related morbidity and mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Chronic Renal Insufficiency Cohort (CRIC) Study revealed a close interaction between cardiac structure and the risk of renal failure in a population with CKD, hypothesizing that cardiac abnormalities and renal damage are based on the same causal pathways, related to the interaction between hypertension, heart failure, and coronary artery diseases [5]. Furthermore, other prognostic evidence has been assessed among adults with CKD, revealing a causal link between adverse cardiac remodeling and increased risk of heart failure-related morbidity and mortality [6].…”
Section: Introductionmentioning
confidence: 99%